Glycogen Storage Disease Type I: Prognostic Factors and Treatment - Moerane, Teboho, Alfred; Kama, Vuyiswa (My University, 2023)
Glycogen storage disease type I (GSD I) is an inherited disorder that hinders the ability of the liver to effectively break down stored glycogen, leading to difficulties in maintaining appropriate blood sugar levels. The main treatment for this aspect of GSD I involves the use of filgrastim, although patients often require additional treatment for recurrent infections, and an enlarged spleen is a common side effect. Acute lactic acidosis, which can cause respiratory distress and ketoacidosis in newborns, can be triggered by minor illnesses and accompanied by severe hypoglycemia. Early diagnosis and prompt initiation of appropriate metabolic treatment are crucial in preventing the devastating effects of this condition. The overall prognosis and long-term efficacy of treatment are influenced by various factors, including the timing of diagnosis, adherence to dietary protocols, and availability of appropriate medical interventions
Keywords: GSD; Prognostic Factors